Oportunidades de mercado para la exportación de café especial de Sandoná Nariño (2020)
The work that will be presented is focused on demonstrating the characterization of special coffee from Sandoná Nariño, describing the current situation in the region, making known the potential, quality and the international commercialization opportunities that the producer could have. Also, it will be presented the shortcomings that the sector currently suffers, which has affected the commercialization opportunity both national and international of a product that is a trend of consumption.